Dark Feathers : Dance of the geisha [videorecording (DVD)] - Huang, Crystal J.; Huang, Crystal J.; Marini, Gilles; Madsen, Michael; Smirnoff, Karen; Lee, Michael (Scatena & Rosner Films, 2025)
Kate must choose loyalty to a historical Asian clan, and her non-traditional love, amidst the deaths of her dance partners being investigated by her new lover.-imdb.com.